Early-childhood social reticence predicts SCR-BOLD coupling during fear extinction recall in preadolescent youth. (April 2019) - Michalska, K.J.; Feldman, J.S.; Ivie, E.J.; Shechner, T.; Sequeira, S.; Averbeck, B.; Degnan, K.A.; Chronis-Tuscano, A.; Leibenluft, E.; Fox, N.A.; Pine, D.S.
Highlights: Threat circuit function may develop differently in children with different temperamental profiles, such as high vs. low social reticence. We relate individual differences in longitudinally assessed, observed socially reticent behavior to brain-physiology interactions during extinction recall. Childhood social reticence predicts a distinct pattern of hemodynamic-autonomic covariation when recalling extinguished threat and safety cues. Covariation patterns indicated that socially reticent youth had difficulty tracking safety as a function of stimulus resemblance to the safe stimulus. Abstract: Social Reticence (SR) is a temperament construct identified in early childhood that is expressed as shy, anxiously avoidant behavior and, particularly when stable, robustly associated with risk for anxiety disorders. Threat circuit function may develop differently for children high on SR than low on SR. We compared brain function and behavior during extinction recall in a sample of 11-to-15-year-old children characterized in early childhood on a continuum of SR. Three weeks after undergoing fear conditioning and extinction, participants completed a functional magnetic resonance imaging extinction recall task assessing memory and threat differentiation for conditioned stimuli. Whereas self-report and psychophysiological measures of differential conditioning, extinction, and extinction recall were largely similar across participants, SR-related differences in brain function emerged during extinction recall. Specifically, childhood SR was associated with a distinct pattern of hemodynamic-autonomic covariation in the brain when recalling extinguished threat and safety cues. SR and attention focus impacted associations between trial-by-trial variation in autonomic responding and in brain activation. These interactions occurred in three main brain areas: the anterior insular cortex (AIC), the anterior subdivision of the medial cingulate cortex (aMCC), and the dorsolateral prefrontal cortex (dlPFC). This pattern of SCR-BOLD coupling may reflect selective difficulty tracking safety in a temperamentally at-risk population.